Physical, Chemical and Biological Characterization of Natural Rubber Latex Membranes Loaded with Cordia verbenacea DC. Extract - Floriano, Juliana F. [UNESP]; Chao, Vitoria de Sousa [UNESP]; Bolognesi, Luis F. C. [UNESP]; Barros, Natan R. de [UNESP]; Miranda, Matheus C. R. [UNESP]; Borges, Felipe A. [UNESP]; Chagas, Ana Laura D. [UNESP]; Paulino, Cristiane G. [UNESP]; Garms, Bruna C. [UNESP]; Marcelino, Monica Y. [UNESP]; Pereira, Juhan A. S. [UNESP]; Santos, Andre G. dos [UNESP]; et al. (Bentham Science Publ Ltd, 2018)
Background and Objective: Cordia verbenacea DC (C. verbenacea) extract has been widely used in Brazilian traditional medicine to treat topical inflammatory processes and has shown healing activity. Moreover, the extract showed activity against coli and Staphylococcus aureus strains. Natural Rubber Latex (NRL) membrane has a potential to stimulate wound healing process, to accelerate healing of cutaneous chronic ulcers in humans, cellular adhesion and increase vascularization Recent studies have used the NRL for Drug Delivery Systems (DDS). In this work, it was developed an NRL membrane was developed containing C. verbenacea using NRL as a carrier and physical, chemical and biological characterization were performed to evaluate its potential as a system release of extract for DDS. Fourier transform infrared spectroscopy (FTIR) showed no chemical interactions between the extract and NRL, which influence its mechanical behavior. C. verbenacea was adsorbed by the NRL membrane along all of its surface. Conclusion: Kinetic release profile showed that NRL membrane can release the extract for up to 18% during 80 hours and it obeys a bi-exponential function. In vitro cytotoxicity and hemolysis assay showed that the extract loaded NRL membrane presented no cell damage effects and no cytotoxicity at a concentration of 100-10%. The results showed that the NRL membrane is a potential and effective model of C. verbenacea release.
Keywords: Natural rubber latex; Cordia verbenacea; NRL membranes; vegetable extract; cytotoxicity; hemolysis; sustained released